Civil Society Against Anti-Pancasila Movements Among Millenial Generation During The Covid-19 Pandemic - Budianti, Yohana Maris (PUSKAPSI Law Review, 2021)
One of the interesting discourses of the decade concerns the discourse against the anti-Pancasila movement. Although the Indonesian government has issued several programs to internalize Pancasila values among the youth generations, citizens are also responsible for protecting the state’s ideology. Accordingly, civil society, as an organized citizen, should catalyze anti-Pancasila movements. Covid-19 pandemic does not only threaten the health sector, but also threatens social activities. Regarding the latter, civil society activists are demanded to adjust to conditions to optimize their function as one of the social infrastructures of a community. Applying, descriptive qualitative approach, the present study aims to see the civil society movements against anti-Pancasila movements during the covid-19 pandemic. The study revealed that civil society is still consistent with its organization despite the dynamics of the implementation.